Factors Associated with Intestinal Obstructions among AdultsinKeysaney Hospital, Mogadishu- Somalia - Moalim, Abdijabar Mohamud; Fiqi, Abdurrahman Osman; Dalmar, Abdirizak Ahmed; TuncEren, -; Ankarali, Handan; Karaman, Muhammet Ihsan; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2018)
Background: Intestinal obstruction (IO) is the failure of propagation of intestinal contents, and may be due to a mechanical or functional pathology. Objective: The aim of this study was to find out the factors, causes, management, and complications associated with IO among adults at KeysaneyHospital. Materials and Methods: A three-year hospital based cross-sectional study was carried out between January 1st, 2014 and December 31st, 2016 with use of the data collected from 180 patients’ medical files including demographics, duration of the disease process, year of admission, hospital stay, causes of IO, operative findings, management, outcomes and complications. Results: In the study group, 148 (82.2%) patients were men, whereas 32 (17.8%) were women, and among all admitted patients, 88 (48.8%) patients lived in Mogadishu. The peak age was between 21-40 years, with a second peak age among elderly patients between 51-70 years. A majority of the patients of 73% presented within more than a week of illness, while 67 (37.2%) patients were discharged within the first week, 47 (26.1%) were discharged within the second week, and 66 (36.6%) stayed in the hospital for more than two weeks. Mechanical obstruction accounted for 142 (78.9%) of all cases. Mechanical small bowel obstruction (SBO) was the most common type with a rate of 61.1%, followed by mechanical large bowel obstruction (LBO) with a rate of 15.6%, while mechanical SBO/LBO was found in 2.2% as compounds of volvulus. Paralytic ileus was found in 9.4% of the cases. The type of obstruction could not be determined in 11.6% of the cases. Overall, adhesions and bands (36.7%) were the most common cause of obstruction followed by strangulated hernias (16.7%) and volvulus (12.7%). Tuberculosis peritonitis (7.8%) was the most common cause of paralytic ileus. Nonoperative management was carried out in 94 (60%) patients while the remaining 64 (40%) cases underwent surgery. Common post-operative complications were wound infection (3.3%) and peritonitis (2.8%). Other rare post-operative complications included wound dehiscence and organ failure. Conclusions: Several factors contribute to either the cause, or the management of IOs. Some of these determinants may include the time since the onset of illness because of late presentation due to lack of health facilities, lack of health awareness, ignorance and poverty. Poor clinical judgment and lack of management guidelines are also the negative factors leading to poor prognosis in these patients. International Journal of Human and Health Sciences Vol. 01 No. 02 July’17. Page : 70-78